ISLAMIC CONSUMPTION BEHAVIOUR AMONG SANTRIWATI: THE ROLE OF LIFESTYLE, PARENTS’ ECONOMIC STATUS, AND SOCIAL ENVIRONMENT - Tia Kholisotun Nafiroh; Yulia Anggraini (RADJA PUBLIKA, 2026)
Rapid social development and cultural transformation in contemporary society have reshaped the consumption patterns of Indonesian adolescents, including female students (santriwati) living in Islamic boarding schools. Although pesantren emphasize modesty, discipline, and value-based education, modern lifestyle trends, family economic conditions, and peer dynamics still influence students’ consumption choices, often leading to behaviors that deviate from Islamic consumption principles. This study aims to examine the influence of lifestyle, parents’ economic status, and the social environment on the Islamic consumption behavior of santriwati at Pesantren Putri Al-Mawaddah. A quantitative research design was employed with a population of 564 students and a sample of 234 respondents selected through stratified random sampling. Data were collected using a structured four-point Likert questionnaire and analyzed using multiple linear regression with SPSS 22. The results indicate that lifestyle, parents’ economic status, and the social environment each have a significant partial effect on Islamic consumption behavior. Furthermore, the three variables jointly exhibit a significant simultaneous effect, suggesting that Islamic consumption behavior among santriwati is shaped by a combination of personal, economic, and social factors. These findings highlight the need for enhanced value-based education, strengthened social control, and systematic internalization of Islamic consumption principles to help students navigate modern influences while maintaining ethical and Sharia-compliant consumption patterns.